Faktor-faktor yang Mempengaruhi Return Saham di Perusahaan Syariah - Puspa Rosiana Syafitri; Rizky Fadhillah; Andriani (Indonesian Journal of Applied Accounting and Finance, 2023)
The goal of every investor is to maximize return, but in the last few decades there have been fluctuations. This is influenced by a number of factors, including Total Asset Turnover (TATO), Return on Asset (ROA), Return on Equity (ROE), and Price to Book Value (PBV). The aim of the study is to determine the impact of TATO, ROA, ROE, and PBV on the return of Islamic stocks in companies listed in the Jakarta Islamic Index group. The research methods used are quantitative and qualitative with a descriptive approach. The population in this study is the entire Islamic companies that are recorded in the Jakarta Islamic Index (JII) during the period 2017-2021 which is as many as 51 companies with samples of 16 companies. Sampling technique used is purposive sampling with data collection methods obtained from the annual reports of related companies. The results of the test of the hypothesis in this study partially showed that TATO has no positive and significant influence on the return of Islamic stocks in Islamic companies, ROA has a positive and signifying influence upon the return on Islamic stocks, ROE does not have a positive or significant effect on the Islamic stock returns, and PBV has not a significant positive influence over the return. Simultaneously, TATO, ROA, ROE, and PBV have an effect on Islamic stock returns.